Mingote, graphic editorialist from Spain - Rodríguez Olaizola, Saturnino (Razón y fe, 2018)
On April 3, 2011, Antonio Mingote died in Madrid. Public opinion, in addition to considering him the best Spanish graphic commentator of the last seventy years, unanimously praised the realism, moderation and affection of his characters. With them he has contributed invaluable to the well-being and good understanding of the Spanish. Catalan by birth, Aragonese by upbringing and Madrid by exercise, Antonio Mingote can and must be considered a model of "awakening" of the national conscience, encouraging our uncertain steps and stimulating national possibility. But above all, Mingote must be valued as an artist who, to be exact, wrote while drawing. This peculiar and unique way ended up making him one of the best Spanish editorialists of the last decades. His editorials, critics have said, fought intransigence, fanaticism, arbitrariness and nonsense.